Cerebral asymmetries in sensory and perceptual processing - Christman, Stephen, 1961- (Advances in psychology (Amsterdam, Netherlands), 1997)
The purpose of the book is to provide a comprehensive overview of hemispheric differences in sensory and perceptual processing. The first section of the book deals directly with the intra- and inter-hemispheric processing of spatial and temporal frequencies in the visual modality. The second section addresses the initial interaction between sensory and cognitive mechanisms, dealing with how the left and right cerebral hemispheres differ in their computation and representation of sensory information. The third section covers how attentional mechanisms modulate the nature of perceptual processing in the cerebral hemispheres. Section four consists of a single chapter which reviews evidence suggesting a functional linkage between upper and right visual field processing, on the one hand, and lower and left visual field processing on the other.